Know your neighbor : Mary Elizabeth Young (The Raton Daily Range Raton, New Mexico, 1965)
Newspaper Article on a little history of Mary Elizabeth Young.
Master list item #: 21
File location is in the Raton File Cabinet
Keywords: Young, Mary Elizabeth; Martin, Clarence; Martin, Clarence (Mrs.); Young, L. Gordon; Williston, Clyde; Mrs. Farr; Moss, Helen; Harris, Herbert (Mrs.); Schiff, Kenneth (Mrs.); Martin, Henry; Martin, Ben; Martin, Bill; Martin, Jim; Michael's Fotoshop; Dockum Drug Company; New Mexico National Gaurd; Wesleyan Service Guild; First Methodist Church; Local History; Biography; Life and Customs; Photography; Family; Raton, New Mexico; Kiowa, Kansas; Lake City, Kansas; Wichita, Kansas; Chicago, Illinois; Capulin, New Mexico; Aransas Pass, Texas; Medicine Lodge, Kansas; Anchorage, Alaska; Albuquerque, New Mexico; Cimarron, New Mexico; Garryowen, Montana